“Turn Around and Forget”: Assessment of the Cognitive Inhibitory Effect of Working Memory Information Using the List-Before-Last Paradigm - Zhao, Xiaojun; Liu, Changhao; Shi, Changxiu (Frontiers in Psychology, 2018)
This study mainly discusses whether the cognitive inhibitory effect of working memory information is affected by the nature of the signified information and the number of retrieval cues in the inhibitory information. Experiment 1 of our study examined the effect of concreteness on the information retrieval phase under different cognitive inhibition scenarios that were distinguished by the nature of the signified information and the number of retrieval cues in the inhibitory information. Experiment 2 of our study examined the effect of the number of retrieval cues in the inhibitory information on the cognitive inhibitory effect under different cognitive inhibition scenarios. The results of both experiments showed that information displaying more concrete characteristics exerted a greater the cognitive inhibitory effect during the working memory task, and a greater cognitive inhibitory effect was produced when all of inhibition retrieval information clues are provided than when none of the clues are provided in the working memory task. Based on these results, the concreteness effect on cognitive inhibition exists, and when all retrieval clues for inhibitory information are provided, the cognitive inhibitory effect might be greater.